How individual characteristics and attitudes shape the job search process of graduates. - Sidonia von Proff (Philipps-University Marburg, Department of Geography, 2015)
Economic factors and individual attitudes have an impact on the mobility of university graduates. At this point of the life, mobility is highest, but still little is known about the process leading to actually starting a job at a certain place. The paper at hand investigates the job search process by means of a graduate survey at two points in time: prior to graduation and one year later. We asked for individual characteristics and attitudes during the job search, ex ante preferred places, and actual locations of the first job. Hence, we are able to show that a spatial focus or certain attitudes during the search do not have an influence on finding a job, but on the duration of the job search. Furthermore, searching at a familiar place does not necessarily lead to a job actually at a familiar place.
Keywords: J61; I23; 330; graduate mobility; regional labour mobility; universities; Germany